(untitled) (Journal of the College of Education for Women, 2019)
Orientalism in all its stage had wrote thousands of studies and researches about Islamic and its civilization. It didn’t leave any side of Islamic culture sides without saying award in it. Orientalists have their studies in Islamic jurisprudence. The study of jurisprudence give the orientalist and opportunity to deeper understanding for Islamic society in the past and nowadays considering that it is a veal application to Islamic general thought. They search in its sources, brunches, history, development, center, ideology, and effect. For this most of orientalist writings in Islamic jurisprudence start from criticism that deny its originality which to be about to gather that Islamic jurisprudence had been affected by non– Islamic resources like: roman low and Talmud.